The DNA-binding activity of transcription factor PTF1 parallels the synthesis of pancreas-specific mRNAs during mouse development. - Petrucco, S (1990)
We have studied the expression of the alpha-amylase, trypsin, and elastase II genes in the acinar pancreas during mouse development. Transcriptional control is the major mechanism by which the differential accumulation of alpha-amylase, trypsin, and elastase II mRNAs is determined during late embryogenesis. The synthesis of pancreatic mRNAs is detected around day 15 of gestation and involves most if not all acinar cells. The DNA-binding activity of the pancreas-specific transcription factor PTF1, which binds to enhancers of genes expressed in this tissue, is detected for the first time at day 15 of gestation. The appearance of the factor at this early stage of development suggests that it plays an important role during pancreas differentiation.